The Design of Things to Come: How Ordinary People Create Extraordinary Products - Vogel, Craig; Cagan, Jonathan; Boatwright, Peter (Pearson, 2005)
The iPod is a harbinger of a revolution in product design: innovation that targets customer emotion, self-image, and fantasy, not just product function. Read the hidden stories behind BodyMedia's SenseWear body monitor, Herman Miller's Mirra Chair, Swiffer's mops, OXO's potato peelers, Adidas' intelligent shoes, the new Ford F-150 pickup truck, and many other winning innovations. Meet the innovators, learning how they inspire and motivate their people, as they shepherd their visions through corporate bureaucracy to profitable reality. The authors deconstruct the entire process of design innovation, showing how it really works, and how today's smartest companies are innovating more effectively than ever before.